Interest Rates Uncertainty, Immediacy Cost and the Role of Banks - Shamshubaridah Ramlee,; Nor Azlan Ghazali, (Asian Academy of Management Journal of Accounting and Finance, 2006)
This study developed the Role of Banks Index (RBX) to characterize the role of banks in delivering its services in an uncertain interest rate and immediate fund requirement environment. We extend the model developed by Ramlee (2001) and Deshmukh, Greenbaum, and Kanatas (1983) by incorporating an element of immediacy costs. The basis of the immediacy cost is in the manner a bank stock up funds as inventory to cater for a loan commitment made to its customer. The strategy adopted in the pooling of funds acts as a penalty cost for borrowing in the last minute. RBX characterizes a banking firm with two possible roles: being a broker when the RBX moved towards 1 and an asset transformer when the RBX moved towards 0. The study successfully operationalized the developed RBX by using a monthly three months KLIBOR rate as a proxy of the uncertain interest rates environment and ?, as the proxy for immediacy costs for the period of 1982 to 2005. We showed that banks act as an asset transformer in an uncertain interest rate and high immediacy costs environment but more as a broker in a stable environment.